Economic Factors Affecting the Return on the Stock Price Index of Service Industry in MAI - Watit Intuluck วาทิต อินทุลักษณ์; Chakrit Srisakun ชาคริต ศรีสกุน (Dusit Thani College Journal, 2018)
The objective of this study is mainly to investigate the predictive power of given economic factors upon stock price index of service industry in the market for alternative investment in Thailand during 2015-2017 (March). The given economic factors include the securities price index of the Stock Exchange of Thailand (SET), MAI stock trading value (TOV), dividend yield (DIV) and Market Cap (MAC). By employing the secondary data derived from MAI database, they were analyzed by using Multiple Linear Regressions with Ordinary Least Squares (OLS). The study found that the securities price index of the Stock Exchange of Thailand (SET), MAI stock trading value (TOV) have negative impact upon stock performance while dividend yield (DIV) and Market Cap (MAC) have positive impact upon stock performance with 73.27 % (which Market Cap has significant effects on DV) of predictive power based on the Multiple Regressions Equation. The study also reveals that Market Cap is the most important economic factor to predict the variance in stock performance of service industry in MAI.